Use of microarray technology for the detection of a range of RNA viruses in clinical samples - Al-Dabbagh, A. G. A (2015)
There are many RNA virus pathogens of humans including influenza, parainfluenza, enteroviruses, parechoviruses, coronaviruses, pneumoviruses, and metapneumoviruses. These commonly invade and infect the respiratory and gastrointestinal tracts, giving rise to acute and chronic respiratory tract infections, and some may also reach the central nervous system (CNS) either via haematogenous or neural routes resulting in a variety of clinical presentations, (e.g. meningitis, encephalitis) which may lead to severe irreparable damage such as poliomyelitis especially in young children. Early correct diagnosis of viral infections is indispensable in order to prevent potential outbreaks which threaten the public health worldwide and might lead to high morbidity and some with significant mortality. Several laboratory techniques such as virus isolation, direct visualization of viral particles, detection of viral antigens and/or nucleic acids, and detection of host immune response (e.g. anti-viral antibodies) to infection, are available for diagnosis, but may have significant drawbacks such as time-inefficiency, cost and certain individual limitations. Microarray technology offers one way to overcome some of these limitations. In this study, a microarray chip containing 7967 oligonucleotides (probes) covering the whole genomes of human enteroviruses, rhinoviruses, respiratory syncytial viruses, metapneumoviruses and influenza viruses was designed and constructed using both OligoArray and Agilent eArray software, to allow simultaneous detection of any of the above viruses present in any clinical specimen. This virochip was tested against positive controls and clinical samples known to contain RNA nucleic acids of these viruses. Viral RNA was reverse transcribed, and amplified. Considerable effort was expended in trying to optimise a multiple displacement amplification (MDA) protocol for whole genome amplification, and in addition, long-range PCR was also utilised. Amplification products were fragmented, labelled and loaded into a hybridization reaction with the designed viral probes printed on the virochip. The results revealed (i) a number of technical problems associated with MDA; (ii) that some probes either failed to recognise their intended targets, or produced cross-reactive signals with non-intended targets; (iii) that many of the designed probes hybridized to their relevant viral nucleic acids and generated hybridization signals of high fluorescent intensity offering an opportunity to develop this probe array in order to be used for the identification of a wide variety of virus species up to the serogroup level or beyond (if required) specifically those causing CNS and respiratory tract infections.